Colonialism and the EU legal order / edited by Hanna Eklund, University of Copenhagen. - Eklund, Hanna (Law in context., 2025)
This book shows how Europe's history of colonialism has shaped the development of the EU legal order. It offers an account of the impact European colonialism has had on the application of law, on the methods of actors, the workings of institutions, and on changes in EU membership over time. Using different case studies, the sixteen chapters of this book address questions concerning how colonial continuities in EU law can be identified; how to understand the present application of EU law through the history of colonialism; and how Europe's colonial history casts new light on EU legal theory and concepts. This book is intended to sharpen analysis of the history, as well as of the present and future application of EU law. This title is also available as open access on Cambridge Core.